Strategi Kesiapsiagaan Menghadapi Bencana Banjir di Perpustakaan SMA Negeri 5 Kabupaten Sinjai - Ilmi, Uswatul; Ardiansyah, Fatri; Sukarman; Achdar HT, M. Nur Rahmat; Tahir, Arsil; Khalik, Idhan; Aryadi, Fadli Rifki; Sabita, Lutfiah; Apreti, Tiara (Inkunabula: Journal of Library Science and Islamic Information, 2025)
This study explores the disaster preparedness strategies of the Library of State Senior High School 5 (SMA Negeri 5) in Sinjai Regency against flood risks. The research aims to identify the strategies implemented and the challenges encountered in mitigating flood disaster impacts in the library. This qualitative descriptive research employed a case study approach, collecting data through participatory observations, semi-structured interviews with school staff, and document analysis. The results indicate that the library has implemented several strategies, including infrastructure improvement, collection digitization, disaster training, early warning system adoption, and stakeholder coordination. However, these efforts face several obstacles, such as limited budgets, inadequate digitization facilities, irregular training sessions, reliance on external early warning systems, and lack of sustainable external coordination. The findings are expected to contribute to the development of disaster risk management practices in school libraries, particularly in flood-prone areas. Abstrak Penelitian ini mengeksplorasi strategi kesiapsiagaan Perpustakaan SMA Negeri 5 Kabupaten Sinjai dalam menghadapi risiko bencana banjir. Penelitian ini bertujuan untuk mengidentifikasi strategi yang diterapkan serta kendala yang dihadapi dalam upaya mitigasi dampak banjir di lingkungan perpustakaan. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan studi kasus. Teknik pengumpulan data dilakukan melalui observasi partisipatif, wawancara semi-terstruktur dengan staf sekolah, serta analisis dokumen. Hasil penelitian menunjukkan bahwa perpustakaan telah menerapkan beberapa strategi, seperti peningkatan infrastruktur, digitalisasi koleksi, pelatihan kebencanaan, penerapan sistem peringatan dini, dan koordinasi dengan pemangku kepentingan terkait. Namun, strategi tersebut masih menghadapi beberapa kendala, di antaranya keterbatasan anggaran, fasilitas digitalisasi yang belum memadai, pelatihan yang tidak rutin, ketergantungan pada informasi eksternal untuk peringatan dini, serta kurangnya koordinasi berkelanjutan dengan pihak luar. Temuan ini diharapkan dapat memberikan kontribusi dalam pengembangan praktik manajemen risiko bencana di perpustakaan sekolah, khususnya di wilayah rawan banjir.